Accounting for Sustainable Development over the Long‐Run: Lessons from Germany. Issue 4 (2nd October 2017) - Blum, Matthias; McLaughlin, Eoin; Hanley, Nick
Abstract: We construct long‐run sustainability indicators based on changes in Comprehensive Wealth – which we refer to as Genuine Savings (GS) – for Germany over the period 1850–2000. We find that German sustainability indicators are positive for the most part, although they are negative during and after the two World Wars and also the Great Depression. We also test the relationship between these wealth changes and a number of measures of well‐being over the long‐run: changes in consumption as well as changes in average height and infant mortality rates. We find a positive relationship between GS and our well‐being indicators over different time horizons, however, the relationship breaks down during WWII. We also test if the GS/Comprehensive Wealth framework is able to cope with massive disinvestment at the end of the Second World War due to war‐related destructions and dismantlement. We find that negative rates of GS were by and large avoided due to the accumulation of technology and growth‐friendly institutions. We demonstrate the importance of broader measures of capital, including measures of technological progress, and its role in the process of economic development; and the limits of conventional measures of investment to understand why future German consumption did not collapse.